Особливості гідравлічного розрахунку водосховища-охолодника системи оборотного водопостачання - Босак, М. (Видавництво Національного університету «Львівська політехніка», 2002)
Hydraulic parameters of water-cooling reservoir of the water-regyling system is investigated in the artikle. An expression for colcculation of the mean velocity of flow in water -cooling rezervoir is proposed.